Peran Publik Perempuan di Indonesia (Perspektif Politik dan HAM) - Hisyam, M Ali (Musawa Jurnal Studi Gender dan Islam, 2004)
The role of Indonesian women within the public sphere is heatedly discussed. The issuance of the Constitution No. 12/2003 is perceived by some people as a "warranty" for a wider opportunity for women in the political realm. Even though the 30 per cent quota for women in the parliament is only a suggestion and not a regulation, this has to be seen as a gateway for women's active role in the public sphere. After a long period of time, especially during the New Order era when women were only allowed to be active in the domestic sphere, this momentum brings a new hope for more freedom for women. This article is an attempt to examine the extent to which women are aware of this opportunity. This includes the examinations of women's readiness in dealing with the cultural barriers and gender bias perspectives on various issueswhich had confined them for quite some times.